1979
DOI: 10.2307/3897131
|View full text |Cite
|
Sign up to set email alerts
|

Komondor Guard Dogs Reduce Sheep Losses to Coyotes: A Preliminary Evaluation

Abstract: Four Komondor dogs were trained to attack captive coyotes and to stay within fenced sheep pastures. The dogs, used in pairs, were then evaluated on three ranches (65 to 330-ha pastures) to determine their potential in protecting sheep from coyote pre. dation. Daily checks of sheep losses were made on each ranch for three consecutive ZO-day periods: preceding placement of the dogs, during their time in pastures, and after their removal. Sheep kills by coyotes decreased significantly during and following use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 5 publications
1
27
1
Order By: Relevance
“…However, sample size was small and the researchers did not make direct observations on LPD behaviour while defending the bait stations. Linhart et al (1979) provided the only field-trial evidence of the effectiveness of LPDs against coyotes. They found that LPDs reduced sheep depredations by coyotes on three ranches over a 20-day period, and coyotes appeared to be displaced from ranches for an additional 20 days after the LPDs were removed.…”
Section: Discussionmentioning
confidence: 99%
“…However, sample size was small and the researchers did not make direct observations on LPD behaviour while defending the bait stations. Linhart et al (1979) provided the only field-trial evidence of the effectiveness of LPDs against coyotes. They found that LPDs reduced sheep depredations by coyotes on three ranches over a 20-day period, and coyotes appeared to be displaced from ranches for an additional 20 days after the LPDs were removed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of LPDs in Europe has resurged as large predator species have recovered (Ribeiro and Petrucci-Fonseca 2004); for example, more than 1000 LPDs are now working in the Alps. In North America, the use ot LPDs has been a relatively recent phenomenon, initiated only in the 1970s (Linhart et al 1979). By 2004, 32% of sheep producers were using LPDs to protect their livestock in the United States (NASS 2005), where LPDs are used principally to protect sheep from coyotes (Cfl;i¿s latrans).…”
Section: History Of Use Of Iivestock Protection Dogsmentioning
confidence: 99%
“…Guard dogs were investigated in the late 1970s and 1980s in the United States (Linhart et al 1979, Green et al 1984 and have been largely incorporated into western US sheep production operations; indeed, by 1993, 65 percent of the sheep producers in Colorado were using guard dogs Hopper 2000). Dogs are thought to be effective against wolves in parts of Europe (Rigg 2001, Fritts et al 2003.…”
Section: Tools and Conceptsmentioning
confidence: 99%